Developing Lexical Competence in Educational Institutions - Maksudova, Dilshoda Kakhramonovna; Qizi, Aliyeva Muxlisa Baxodir (PT. Antis International Publisher, 2024)
This article is importance of lexical skills in the context of interdisciplinary relations as an integral part of the lexical competence of a foreign language is emphasized, their specificity and conditions of formation are described, based on the advantage of constructing a lexical competence of a foreign language on an interdisciplinary basis. This involves taking into account the linguistic characteristics of the students as well as the educational and cognitive activities.